High occurrence of mitochondrial heteroplasmy in nepalese indigenous sheep (Ovis aries) compared to chinese sheep - Gorkhali, N.A.; Lin Jiang; Shrestha, B.S.; Xiao-Hong He; Qian-Jun Zhao; Han Jianlin; Yue-Hui Ma (Informa UK Limited, 2016)
Heteroplasmy due to length polymorphism with tandem repeats in mtDNAs within individual was hardly studied in domestic animals. In the present study, we identified intra-individual length variation in the control region of mtDNAs in Nepalese sheep by molecular cloning and sequencing techniques. We observed one to four tandem repeats of a 75-bp nucleotide sequences in the mtDNA control region in 45% of the total Nepalese sheep sampled in contrast to the Chinese sheep, indicating that the heteroplasmy is specific to Nepalese sheep. The high rate of heteroplasmy in Nepalese sheep could be a resultant of the mtDNA mutation and independent segregation at intra-individual level or a strand slippage and mispairing during the replication.